Malignant neoplasms of the lips, oral cavity and pharynx – state of the problem - Rybachuk, Ann; Hbur, Zoriana; Zavada, Oksana; Krylova, Irina (Journal of Education, Health and Sport, 2021)
The aim: to consider the existing methods of diagnosis, clinical course and treatment of most common malignant tumors of soft tissues of maxillofacial area and oral cavity. Materials and methods. Method of economical analysis, method of system analysis, medical – statistical method, mathematical modeling method, information-analytical method. Results. Types and clinic of the most widespread tumors of the specified area are considered. The technique of examination at the specified pathology with use of auxiliary methods of diagnostics is described. The main methods of special treatment of cancer patients are mentioned. The clinical course of four stages of maxillofacial cancer was analyzed on the example of lip cancer. It is confirmed that morphological methods are the most informative of all currently available diagnostic tools and their brief description is given. Conclusions. Early diagnosis of malignant neoplasms, timely recognition and treatment of precancerous conditions against which cancer develops, is the main task of a general practitioner for the prevention of cancer. The dentist at the stage of planned rehabilitation of the oral cavity should pay attention to all changes in the mucous membrane. The formation of high-risk cancer groups and their in-depth examination can increase and detect precancerous diseases and malignant neoplasms in the early stages, which can serve as a real basis for the prevention of cancer of the maxillofacial region, oral mucosa, tongue and lips.